Resposta dinâmica de camadas magnéticas acopladas - Lima, Ana Tereza de Abreu (2007)
We study the dynamical behavior of systems constituted of two coupled magnetic lms. We consider that the coupling of the lms can be represented by an interaction like Heisenberg to have the magnetic susceptibility of each medium, taking into account the presence of interface e ect and the neighboring layer. Through the calculation of the magnetization of the system, we found an expression for the susceptibility of the coupled system, which can be understood as a weighed mean of the susceptibility of the media that compose the system. Our results can be used to have the dynamic behavior of any magnetic bilayer. We use the result to calculate the dispersion relation of polaritons propagating in a magnetic bilayer consisting of an antiferromagnetic layer grown in direct contact with a ferromagnetic lm. Numerical results were obtained for a system where the antiferromagnetic material is MnF2 and the ferromagnetic is Fe. The results of the dispersion relation are con rmed through the calculation of the re ectivity of a Attenuated Total Re exion (ATR) experiment.